The major issues of incoming presidential election in the republic of Somaliland - Muse, Mohamamud Yousuf; Shuriye, Abdi Omar (Australian Journal of Islamic Studies, 2018)
The Republic of Somaliland which is located in the Horn of Africa with the approximate population of 3.85 million is a self-declared state that announced its secession from Somalia in 1991. Since then, the republic has been fighting for the full independ, hence and international recognition as well. Perhaps, the case of Somaliland is vague and unknown to many people. This study therefore attempts to discuss and shed the light on the major aspects related to the issue, especially the major issues of incoming presidential election in the Republic of Somaliland. The study also provides a brief historical events of Somalia from its establishment till the secession of Somaliland. The study as well gives the details of the activities of all the governments of Somaliland from its Separation till date. Therein, the main characteristics that distinguish one government from the other, such as their achievements and their lapses have been analyzed. The study likewise focuses on some predictive scenarios of Somaliland forthcoming presidential election to be held on November 13, 2017. Lastly, the study emphasizes the role of tribal affiliation, vote buying and the interest of international organizations in influencing the forthcoming presidential election in particular and the general political affairs of Somaliland. The primary pattern of this study is chronological in nature, where the related issues are discussed sequentially. It starts the discussion with the historical brief of Somalia from its establishment till the secession of Somaliland, followed by the activities of Somaliland government from its separation till date, as well as some predictive scenario of Somaliland incoming governments.